Peculiarities of Adults` Physical Recreation through WUSHU Martial Arts - Darius Liviu POPESCU; Angela POLEVAIA-SECĂREANU; Ecaterina LUNGU (ACROSS)
In this research, the characteristics of physical recreation as a type of physical culture were described and also its main characteristics were highlighted. WUSHU martial arts is considered to be one of the possible ways to organize the physical recreation of adults, presenting its differences and specificity.